2018
DOI: 10.1038/s41467-017-02401-7
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine directly interacts and activates the angiotensin II type I receptor to aggravate vascular injury

Abstract: Hyperhomocysteinemia (HHcy) is a risk factor for various cardiovascular diseases. However, the mechanism underlying HHcy-aggravated vascular injury remains unclear. Here we show that the aggravation of abdominal aortic aneurysm by HHcy is abolished in mice with genetic deletion of the angiotensin II type 1 (AT1) receptor and in mice treated with an AT1 blocker. We find that homocysteine directly activates AT1 receptor signalling. Homocysteine displaces angiotensin II and limits its binding to AT1 receptor. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(117 citation statements)
references
References 56 publications
3
112
0
2
Order By: Relevance
“…D, intramolecular BRET of the SSH2-FlAsH biosensors in response to NRG stimulation (50 ng/ml NRG, 40 min). The BRET biosensor of the AT1R was used as a negative control (59). The SSH2-23-FlAsH, SSH2-63-FlAsH, and AT1R-FlAsH (23) were transiently transfected in MCF-7 cells, starved for 2 h, and then stimulated with 50 ng/ml NRG or control vehicle for 40 min.…”
Section: Steady-state Kineticsmentioning
confidence: 99%
“…D, intramolecular BRET of the SSH2-FlAsH biosensors in response to NRG stimulation (50 ng/ml NRG, 40 min). The BRET biosensor of the AT1R was used as a negative control (59). The SSH2-23-FlAsH, SSH2-63-FlAsH, and AT1R-FlAsH (23) were transiently transfected in MCF-7 cells, starved for 2 h, and then stimulated with 50 ng/ml NRG or control vehicle for 40 min.…”
Section: Steady-state Kineticsmentioning
confidence: 99%
“…10 Recent data have demonstrated that Hcy directly interacted and activated with AT1R to aggravate adventitial in ammation, collagen accumulation, and vascular injury. 1,2,9 However, little is known about the possible mechanisms by which Hcy can promote AFs migration and invasion and accelerate atherosclerosis formation via AT1R activation. This study revealed that Hcy induced AFs migration and invasion, which was inhibited with telmisartan treatment, an AT1R inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is a nonessential sulfur-containing amino acid derived from the essential amino acid methionine and actively participates in various biochemical reactions. 1 HHcy (circulating Hcy ≥ 15 µ m) is an independent risk factor for many cardiovascular diseases, such as atherosclerosis, coronary heart disease, and abdominal aortic aneurysm. Although there is evidence that HHcy can cause vasodilation, damage endothelial cells, promote intravascular proliferation, promote outer membrane activation, and disrupt hemostasis/coagulation, [2][3][4][5] the mechanism by which Hcy aggravates atherosclerosis remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homocysteine (Hcy) is a thiol containing non‐protein amino acid involved in methionine´s metabolism that is considered a biomarker of cardiovascular and neurodegenerative diseases . Few works reported the chiral separation of Hcy by HPLC and only two works employed CE for this purpose .…”
Section: Introductionmentioning
confidence: 99%